Potential exposure of a classical biological control agent of the soybean aphid, Aphis glycines, on non-target aphids in North America - Wyckhuys, Kris A.G.; Koch, RL; Kula, RR; Heimpel, George E. (Springer, 2009)
In summer 2007, the Asian parasitoid Binodoxys communis (Hymenoptera: Braconidae) was released in North America for control of the exotic soybean aphid, Aphis glycines (Hemiptera: Aphididae). Despite its comparatively narrow host range, releases of B. communis may still constitute a risk to native aphid species. To estimate the risk of exposure of non-target aphids to B. communis, we merged assessments of temporal co-occurrence with projections of spatial overlap between B. communis and three native aphid species, and in-field measurements of the incidence of ecological filters that may protect these aphids from parasitism. Temporal co-occurrence was assessed between A. glycines and native aphids (Aphis asclepiadis, Aphis oestlundi, and Aphis monardae) at four different locations in Minnesota, USA. The degree of temporal overlap depended greatly on location and aphid species, ranging between 0 and 100%. All of the native aphids were tended by multiple species of ants, with overall ant-attendance ranging from 26.1 to 89.6%. During temporal overlap with A. glycines, 53 ± 11% of A. monardae colonies were partly found in flower heads of their host plant, with flowers acting as a physical refuge for this aphid. The extent of geographic overlap between B. communis and native aphids based upon Climex modeling was 17 28% for A. monardae, 13 22% for A. oestlundi, 46 55% for A. asclepiadis and 12 24% for the A. asclepiadis species complex. The estimated overall probability of potential exposure of B. communis on native aphids was relatively low (P = 0.115) for A. oestlundi and high (P = 0.550) for A. asclepiades. Physical and ant-mediated refuges considerably lowered probability of population-level impact on A. monardae, and could lead to substantial reduction of exposure for the other native aphids. These findings are used to make broader statements regarding the ecological safety of current B. communis releases and their potential impact on native aphid species in North America.